Characterizing the production of small-scale tree seed nurseries in Burkina Faso: Insights from a national survey - Oubida, Wendpouiré Régis; Daboue, Edith Marie Sylvie; Bama, Wend-Kuni Josée; Sougué, Bassirou Moïtché; Ouedraogo, Moussa; Vinceti, Barbara (Springer Nature, 2025)
Effective tree-based restoration depends on robust seed systems capable of supplying diverse, high-quality planting material. Burkina Faso is an active participant in the Great Green Wall initiative, but the main features and performance of small-scale tree nurseries remain poorly characterized. This study aimed to assess their production and presents results from the largest survey of this kind ever conducted in Burkina Faso. Managers of 596 small private nurseries across eight regions of Burkina Faso were engaged in a survey. Data were collected on species diversity, production volumes, seed procurement, technical capacity, and challenges affecting nursery operations. The survey revealed that nursery production included 248 different plant species, of which 53% were exotic with a significant share of ornamental plants, particularly in nurseries located near large urban areas. A total of 133 tree species were recorded, about half of them native. Tree seedlings represented the bulk of the production. Seed sourcing occurred mainly locally, and genetic quality did not appear to be a significant concern for nursery managers. Water scarcity, weak market linkages, and inadequate infrastructure emerged as the most pressing challenges. Most nurserymen had received training, though knowledge gaps persisted in seed handling and propagation management. Overall, it appears that small-scale nurseries form a crucial but under-supported component of Burkina Faso’s tree seed system. Strengthening this sector requires improving access to water and infrastructure, expanding training on native species propagation and seed quality, better targeted seed collection, and enhanced market and distribution networks.